ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE PERIOD ORDER QUANTITY (POQ) PADA USAHA ROTI KAMPAR BAKERY - Muhammad Fahrul Azwan; Suarni Norawati (STIE Bangkinang Publishing, 2019)
Bread Business Kampar Bakery Bangkinang is a company engaged in food processing namely bread. The products produced are white bread and sweet bread. The purpose of this study is to analyze the inventory of bread raw materials by using the period order quantity (POQ) method. The period order quantity method is one method of controlling inventory by emphasizing the effectiveness of order frequencies in order to save total inventory costs. From the results of research conducted, it can be concluded that using the period order quantity (POQ) method can save inventory costs by Rp. 3,783,124.